ARAH FORMULASI KEBIJAKAN KOMUNIKASI - Ana Nadhya Abrar (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2004)
Law No.32, 2002, was formed in response to the problems society has faced for approximately four years regarding the absence of laws governing the broadcast media (lawless broadcasting era). In reality, the presence of this law has not been accepted by those involved in broadcast media and has resulted in the criticism of this law by such parties. Several questions have been raised by these criticisms, mainly: What direction does the formulation of Law No.32, 2002 lead? In response to this question the writer examines the passages of the Law qualitatively. This has lead to the discovery that the formulation of Law No. 32, 2002, is not conducive to the building of a healthy Indonesian democracy. The direction of the formulation of the rules governing broadcast media as laid out in Law No.32, 2002are believed to be incapable of being useful within a civil society. Because of this, the writer presents an alternative method for the formulation of the direction for appropriate communication. This is achieved through combining issues of the communication media in Indonesia by outlining the primary characteristics of the mass media, social media and interactive media from their respective positions.